New excited states in the halo nucleus $^6$He - X. Mougeot; V. Lapoux; W. Mittig; N. Alamanos; F. Auger; B. Avez; D. Beaumel; Y. Blumenfeld; R. Dayras; A. Drouart; C. Force; Gaudefroy, L.; et al. (Phys. Lett. B, 2012)
The low-lying spectroscopy of 6He was investigated via the 2-neutron transfer reaction p ( He 8 , t ) with the 8He beam delivered by the \{SPIRAL\} facility at 15.4   A MeV . The light charged particles produced by the direct reactions were measured using the \{MUST2\} Si-strip telescope array. Above the known 2 + state, two new resonances were observed: at E ⁎ = 2.6 ± 0.3   MeV (width Γ = 1.6 ± 0.4   MeV ) and at 5.3 ± 0.3   MeV with Γ = 2 ± 1   MeV . Through the analysis of the angular distributions, they correspond to a 2 + state and to an L = 1 state, respectively. These new states, challenging the nuclear theories, could be used as benchmarks for checking the microscopic inputs of the newly improved structure models, and should trigger development of models including the treatments of both core excitation and continuum coupling effects.
Keywords: He 8 ( p; t )